2021
DOI: 10.1155/2021/6644937
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Construction, Operation, and Maintenance of a Large Wastewater‐Treatment Plant Based on BIM

Abstract: Building information modeling (BIM) is a data-based tool for engineering, design, and building management, which is used to parameterize and model various types of information. This information may then be shared and introduced throughout the building life-cycle phases (planning, design, construction and operation, and maintenance (O&M)). Therefore, BIM allows engineers to correctly understand and efficiently respond to varying types of building information as well as serves as a foundation for cooperation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Bee Hua Goh, based on information on parameters related to LCC, investigated a model analysis method for estimating the whole life cycle cost of green buildings, and it was concluded that the traditional LCC measurement needs to be improved [34]. Li Zhong Fu assigned the comprehensive benefit evaluation index of BIM green building O&M management with the help of the COWA operator, established a comprehensive benefit evaluation model and method, and determined the advantageous role of BIM in green building O&M management [27]. Cao Yu et al studied the application of BIM technology in the construction process of green buildings and found that BIM technology is used in green building construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bee Hua Goh, based on information on parameters related to LCC, investigated a model analysis method for estimating the whole life cycle cost of green buildings, and it was concluded that the traditional LCC measurement needs to be improved [34]. Li Zhong Fu assigned the comprehensive benefit evaluation index of BIM green building O&M management with the help of the COWA operator, established a comprehensive benefit evaluation model and method, and determined the advantageous role of BIM in green building O&M management [27]. Cao Yu et al studied the application of BIM technology in the construction process of green buildings and found that BIM technology is used in green building construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on BIM technology and big data monitoring and analysis of the use status of buildings, a dynamic digital model can be established to realize visual management. Through the analysis and comparison of building reliability, economy and energy consumption, the management and supervision mode of construction equipment operation is summarized to promote the wisdom of daily operation and maintenance [5], so as to reduce operation and maintenance costs. The establishment of the late operation and maintenance system is conducive to improving the management mode and promoting the benign competition in the market.…”
Section: Operation and Maintenance Stagementioning
confidence: 99%
“…52339/tjet.v42i3.953 While the use of AI in power plant maintenance is beginning to take foothold, there has been a number of studies on the deployment of the technique in predictive maintenance applications in different environmental installations generally. In the literature abounds the applications of ML in facilities other than power systems (Bahri et al, 2009;Brahm de Jong, 2015;Bayoumi and McCaslin, 2017;Vuyyuru, 2018;Ahmad et al, 2018;Pai et al, 2019;Long et al, 2020;Niyonambaza et al, 2020;Girit et al, 2021;Miao, 2021;Li et al, 2021;Wei et al, 2021). In similarly vein, Hua et al (2020), Olesen and Shaker (2020) and Yang et al (2020) are instances of several cases of deploying ML in power systems infrastructures other than thermal generating plants.…”
Section: Introductionmentioning
confidence: 99%